Leaving the Academic Niche–Rhoda Erdmann (1870–1935) and the Democratization of Tissue Culture Research - Fangerau, Heiner (Frontiers in Cell and Developmental Biology, 2022)
In the years after Ross Harrison published his pivotal paper on nerve fiber regeneration in 1907, researchers following his line of research presented tissue culture techniques as an extremely sensitive, difficult, and almost occult methodology. When Philip R. White published a manual on tissue culturing in 1954, he declared that he wanted to disenchant this formerly mystified field of study. With a similar aim Rhoda Erdmann had published a comparable manual more than 30 years before in 1922. Her intention was to offer a book that would make the method “a common property of those who want to do biological research in the future.” When science was about to move from little science to big science, Erdmann tried to democratize tissue culture knowledge. Rhoda Erdmann was in many aspects an extraordinary scholar deviating from the norm. She was one of the few women in the field, working as a low-level assistant at the Robert Koch Institute in Berlin before she took the opportunity to work as a research fellow with Ross Harrison in Yale. She was imprisoned during the First World War on the accusation of being a German spy. After she could return to Germany in 1919, she established a laboratory for experimental cell research in Berlin. In 1929 she was one of the first women to be appointed a professor in Germany. The paper focuses Erdmann’s attempts at distributing practical tissue culturing knowledge. Based on her and other scholars’ research work on nutrient media for cell cultures, and the attempts to optimize these basic tools for different species, this contribution examines the hypothesis that this work constituted an academic niche for underprivileged scientists. The paper analyzes whether Erdmann, due to her extraordinary characteristics, had to use certain niches in the academic world (topics, places, techniques, communities) to pursue her research, and whether her attempts at democratizing her techniques can also be read as an attempt to move out of the niche to gain academic recognition.